The April 2015 Update to RDA and Its Impact on Music Instructions: A Review of What Music Cataloguers Need to Know - Paradis, Daniel; Hafner, Joseph (CAML Review / Revue de l'ACBM, 2015)
The April 2015 release of the RDA Toolkit includes major content updates to RDA: Resource Description and Access. Several of the revisions included in the release modify instructions that are used by music cataloguers on a regular basis. This article reviews the most important of these changes with the purpose of making it easier for music cataloguers to navigate the various changes that have taken place in relation to music cataloguing. It examines specifically the impact of the revisions regarding the statement of responsibility, the extent of notated music, the duration, preferred titles of musical works, abbreviations in titles for parts of musical works, and access points representing musical expressions. The article illustrates some of the changes by including examples that were revised or added. It also includes a table which is a comparison of the structure of 6.14.2 instructions before and after the April 2015 update, because of the numerous changes in this area. While this article is aimed primarily at music cataloguers, it could also be of interest to music librarians concerned with cataloguing issues.